Breast Reconstruction in Private Practice - Pisano, Steven M. (Thieme Medical Publishers, 2004)
Comprehensive breast reconstruction can be performed in private practice. Our practice philosophy is that autogenous tissue provides the best substrate for breast reconstruction; the deep inferior epigastric perforator flap is our primary method of breast reconstruction. Microsurgical training and a group practice model permit routine use of all autogenous tissue techniques. Office, operating room, and hospital teams must be assembled; these teams follow clinical pathways, which make the execution of reconstructive procedures consistent and efficient. The practice must implement a plan for physician and patient education. The practice must review clinical outcomes, making adjustments in operative techniques and pre- and postoperative clinical pathways so that the best results can be achieved with a low complication rate. Breast reconstruction is a core service of our practice. We have accrued an economy of scale including these features: intraoperative and clinical efficiency, low practice overhead costs, and a high patient satisfaction rate.